COMPARATIVE ALLOCATIVE EFFICIENCY AND PROFITABILITY OF DIFFERENT SCALES OF POULTRY-EGG PRODUCTION IN JOS METROPOLIS, PLATEAU STATE, NIGERIA - Folorunso, Solomon T.; Omosebi, T.; Agbonika, D. A. (FUDMA JOURNAL OF SCIENCES, 2021)
The study compared the allocative efficiency and profitability of poultry-egg farmers in Jos metropolis of Plateau State, Nigeria, across different scales. To select 143 respondents, a two-stage sampling technique was used. Using well-structured questionnaire and interview schedules, primary data on socioeconomic variables were collected. Collected data were analyzed using budgetary technique and stochastic production frontier model. Result of allocative efficiency showed the following: The mean allocative efficiency of the small, medium and large scales was 0.68, 0.12 and 0.11 respectively; the minimum allocative efficiency for small, medium and large scales was 0.30, 0.10 and 0.10 respectively. The maximum allocative efficiency was 0.59, 0.18 and 0.11 respectively for small, medium and large scale farmers. The profitability result indicated that egg production for small, medium and large-scale farms was profitable in the study area with N675, 671.79, N4, 897,236.09 and N16, 327,633.66 per farmer. The rate of return on investment per bird was found to be 19.51%, 31.21% and 83.13% respectively for small, medium and large farm sizes. For small, medium and large-scale farmers respectively, the capital turnover per bird was N 1.20, N1.31 and N1.83. Also, the profitability indices for the small, medium and large scales are N0.16, N0.24 and N0.45. The study recommends that; Farmers should be advised to increase production from small scale to large scale through policies that will promote such, special intervention is needed from the government at all levels through farmers’ cooperatives in the area of inputs subsidy, price efficiency of the farmers could